Exploring NFTs in the Fashion Industry: Challenges and Prospects for future regulation - Alcántara Francia, Olga Alejandra (2023)
This article examines the impact and the growing adoption of non-fungible tokens (NFTs) in the fashion industry, highlighting their influence on authenticity, digital ownership, and the interaction among creators, consumers, and brands. As blockchain and NFT technologies continue to reshape the fashion landscape, this study explores their implications in the fashion ecosystem and the challenges they pose in terms of copyright.The article begins by exploring how NFTs enable fashion designers to authenticate their creations, providing a solution to counterfeiting and copying issues. Additionally, it emphasizes the NFTs’ capacity to track the ownership of digital assets, which can lead to greater control and compensation for fashion designers and artists.However, as the fashion industry delves into the world of NFTs, legal and ethical challenges emerge in relation to copyright. The article addresses issues related to the protection of intellectual property and the need for clear regulations in the NFT space.